2015
DOI: 10.1007/s10751-015-1127-y
|View full text |Cite
|
Sign up to set email alerts
|

Mossbauer and XRD characterization of the phase transformations in a Fe-Mn-Al-C-Mo-Si-Cu as cast alloy during tribology test

Abstract: In present study Fe-29.0Mn-6Al-0.9C-1.8Mo-1.6Si-0.4Cu (%w) alloy was obtained after melted in an induction furnace, and then molded as an ingot. From the as cast ingot it were cut samples for the different characterization measurements. The microstructure of the as-cast sample is of dendritic type and its XRD pattern was refined with the lines of the austenite, with a big volumetric fraction, and the lines of the martensite, with small volumetric fraction. The Mössbauer spectrum of the sample was fitted with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…This can be interpreted as a consequence of the thermal treatments, which produce martensite in the Fermanal sample, and this phase improves the mechanical properties of steel. The wear test on Fermanal steel increases the martensite fraction, improving its mechanical properties, as reported by Ramos et al [8].…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…This can be interpreted as a consequence of the thermal treatments, which produce martensite in the Fermanal sample, and this phase improves the mechanical properties of steel. The wear test on Fermanal steel increases the martensite fraction, improving its mechanical properties, as reported by Ramos et al [8].…”
Section: Discussionsupporting
confidence: 58%
“…After the development of Hadfield steels, other alloys based on the steel concept of this austenitic manganese steel with varying compositions followed [7]. One such alloy is the Fe-Mn-Al-C alloy or "Fermanal" steel, which was developed to replace some conventional stainless steels (Ni-Cr steels) [8]. This austenitic steel exhibit a good strain hardening behavior and is considered to be an economic substitutes for conventional austenitic stainless steels because it contains aluminum and manganese instead of chromium and nickel [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that in this investigation the precipitation of the κ-carbides was produced by the conventional treatment of quenching + aged, where it was observed that the carbides precipitate along grain boundaries, thus causing brittleness. Another interesting work was performed by Ramos et al (2015) [243] who studied the abrasive wear of a Fe-29.0Mn-6Al-0.9C-1.8Mo-1.6Si-0.4Cu steel in "as cast" condition. In this work, they found that the austenite was transformed into martensite during the wear process.…”
Section: Abrasive Wearmentioning
confidence: 99%
“…Another interesting work was performed by Ramos et al (2015) [243] who studied the abrasive wear of a Fe-29.0Mn-6Al-0.9C-1.8Mo-1.6Si-0.4Cu steel in "as cast" condition. In this work, they found that the austenite was transformed into martensite during the wear process.…”
Section: Abrasive Wearmentioning
confidence: 99%